PENGARUH SIKAP DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT BOSOWA BERLIAN MOTOR DI MAKASSAR - Zainal Abidin (Jurnal Bisnis dan Kewirausahaan, 2016)
This study aims to identify and analyze variables influence attitudes and organizational commitment to employee performance at PT Bosowa Berlian Motors in Makassar.Populasi in this study were all employees of PT Bosowa Berlian Motors in Makassar, amounting to 230 people. While the determination of the number of samples determined by using Slovin approach, in order to obtain a sample of 70 people .. The data analysis technique used is multiple linear regression. Attitudes and organizational commitment significantly influence the performance of employees of PT Bosowa Berlian Motors in Makassar. In between these two factors were included as predictors, the attitude factor is the factor most dominant influence on the performance of employees of PT Bosowa Berlian Motors in Makassar.